A novel photonic crystal band-pass filter using degenerate modes of a point-defect microcavity for terahertz communication systems - Chun-Ping, Chen; Anada, Tetsuo; Greedy, Steve; Benson, Trevor M.; Sewell, Phillip (Wiley, 2014)
Compact devices are important for the realization of terahertz communications systems. This article proposes a novel photonic crystal-based device for realizing microminiature, high-selectivity high Q band-pass filters (BPF) and the design of a dual-mode square lattice photonic crystal BPF that utilizes the degenerated modes of a point defect microcavity is presented. To design a high Q microcavity, the photonic band-gap is initially calculated using the plane wave expansion method. Second, the eigenfrequencies and modal fields of a point defect microcavity that generates localized states in the band-gap are calculated by a supercell method. Finally, the characteristics of mode splitting and the proposed dual-mode BPFs are numerically studied by a full-wave time-domain method.